Program Inovasi “Gerakan Ibu Pintar Atasi Kurang Gizi” (GITAR AKZI) di Desa Panggungrejo Kecamatan Tulungagung - Widi Astuti, Wuri; Andri Mustofa, Linda (STIKES dan AKZI Karya Husada Kediri, 2024)
The prevalence of toddlers in the category of malnutrition status in Indonesia reaches 13% and the death rate caused by malnutrition reaches 54%. There are several factors that cause toddlers to have poor nutritional status, including the mother's nutritional knowledge. The Innovation Program